Red blood cells treated with the amustaline (S‐303) pathogen reduction system: a transfusion study in cardiac surgery. Issue 4 (1st March 2018) - Brixner, Veronika; Kiessling, Arndt‐Holger; Madlener, Katharina; Müller, Markus M.; Leibacher, Johannes; Dombos, Sarah; Weber, Iuliia; Pfeiffer, Hans‐Ulrich; Geisen, Christof; Schmidt, Michael; Henschler, Reinhard; North, Anne; et al.
Abstract : BACKGROUND: Nucleic acid–targeted pathogen inactivation technology using amustaline (S‐303) and glutathione (GSH) was developed to reduce the risk of transfusion‐transmitted infectious disease and transfusion‐associated graft‐versus‐host disease with red blood cell (RBC) transfusion. STUDY DESIGN AND METHODS: A randomized, double‐blind, controlled study was performed to assess the in vitro characteristics of amustaline‐treated RBCs (test) compared with conventional (control) RBCs and to evaluate safety and efficacy of transfusion during and after cardiac surgery. The primary device efficacy endpoint was the postproduction hemoglobin (Hb) content of RBCs. Exploratory clinical outcomes included renal and hepatic failure, the 6‐minute walk test (a surrogate for cardiopulmonary function), adverse events (AEs), and the immune response to amustaline‐treated RBCs. RESULTS: A total of 774 RBC unis were produced. Mean treatment difference in Hb content was –2.27 g/unit (95% confidence interval, –2.61 to –1.92 g/unit), within the prespecified equivalence margins (±5 g/unit) to declare noninferiority. Amustaline‐treated RBCs met European guidelines for Hb content, hematocrit, and hemolysis. Fifty‐one (25 test and 26 control) patients received study RBCs. There were no significant differences in RBC usage or other clinical outcomes. Observed AEs were within the spectrum expected for patients of similar age undergoing cardiovascular surgery requiring RBCs transfusion. No patients exhibited an immune response specific to amustaline‐treated RBCs. CONCLUSION: Amustaline‐treated RBCs demonstrated equivalence to control RBCs for Hb content, have appropriate characteristics for transfusion, and were well tolerated when transfused in support of acute anemia. Renal impairment was characterized as a potential efficacy endpoint for pivotal studies of RBC transfusion in cardiac surgery.